Cerebrospinal fluid soluble TREM2 in aging and Alzheimer's disease. Issue 1 (December 2016) - Henjum, Kristi; Almdahl, Ina; Årskog, Vibeke; Minthon, Lennart; Hansson, Oskar; Fladby, Tormod; Nilsson, Lars
Abstract Background Alzheimer's disease (AD) neuropathology is associated with neuroinflammation, but there are few useful biomarkers. Mutant variants of triggering receptor expressed on myeloid cells 2 (TREM2) have recently been linked to late-onset AD and other neurodegenerative disorders. TREM2, a microglial receptor, is involved in innate immunity. A cleaved fragment, soluble TREM2 (sTREM2), is present in the cerebrospinal fluid (CSF). Methods We developed and used a novel enzyme-linked immunosorbent assay to investigate the potential value of CSF sTREM2 as an AD biomarker in two independent cohorts: an AD/mild cognitive impairment (MCI)/control cohort (n  = 100) and an AD/control cohort (n  = 50). Results We found no significant difference in sTREM2 levels between groups of controls and patients with AD or MCI. However, among all controls there was a positive correlation between sTREM2 and age (Spearman rho = 0.50;p  < 0.001;n  = 75). In the AD/MCI/control cohort, CSF sTREM2 correlated positively with total Tau (T-tau) (Spearman rho 0.57;p  < 0.001;n  = 50), phosphorylated Tau (P-tau) (Spearman rho 0.63;p  < 0.001;n  = 50) and amyloid-β1–42 (Aβ42) (Spearman rho 0.35;p  = 0.01;n  = 50) in control subjects. Among controls with a CSF Aβ42 above a cut-off value (700 pg/ml) in this cohort, the positive correlation between sTREM2 and Aβ42 was stronger (Spearman rho = 0.44;p  = 0.002;n  = 46). Conclusions sTREM2 in CSF correlates with aging in controls, and with the neurodegenerative markers CSF T-tau/P-tau among controls who are negative for AD CSF core biomarkers Aβ42, T-tau or P-tau.